5(y+2)=-2(12+9y)+y

Simple and best practice solution for 5(y+2)=-2(12+9y)+y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(y+2)=-2(12+9y)+y equation:


Simplifying
5(y + 2) = -2(12 + 9y) + y

Reorder the terms:
5(2 + y) = -2(12 + 9y) + y
(2 * 5 + y * 5) = -2(12 + 9y) + y
(10 + 5y) = -2(12 + 9y) + y
10 + 5y = (12 * -2 + 9y * -2) + y
10 + 5y = (-24 + -18y) + y

Combine like terms: -18y + y = -17y
10 + 5y = -24 + -17y

Solving
10 + 5y = -24 + -17y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '17y' to each side of the equation.
10 + 5y + 17y = -24 + -17y + 17y

Combine like terms: 5y + 17y = 22y
10 + 22y = -24 + -17y + 17y

Combine like terms: -17y + 17y = 0
10 + 22y = -24 + 0
10 + 22y = -24

Add '-10' to each side of the equation.
10 + -10 + 22y = -24 + -10

Combine like terms: 10 + -10 = 0
0 + 22y = -24 + -10
22y = -24 + -10

Combine like terms: -24 + -10 = -34
22y = -34

Divide each side by '22'.
y = -1.545454545

Simplifying
y = -1.545454545

See similar equations:

| 3.3-3y=7 | | t(x)=6+3x-2 | | k^2=-2k+24 | | (-5a^2b)(3a^2b^2)=x | | .5*-6=4 | | 5x+12=-11x | | 9-2logx=10 | | 7(1+y)=-3(y+2) | | 27m=135 | | -3m-4=10m | | d(x)=12-0.25x | | 12x=-4x+2 | | 21+4=16 | | 8cosx-2=0 | | 2x+5(4x+19)=205 | | 7+4c=10 | | x+10/4=7 | | -10-4n^2=-330 | | N+3=21 | | h(x)=7-2x | | 4.5m+(-3.2m)-13=-2.63 | | 9x-4(x-3)=712 | | 92=72+4h | | 9m=51 | | 9z=20+16 | | ((2)3.14+(1.125)3.14)= | | 27=9a | | 16-c=18 | | v^2-5=4v | | -9(-10x-25)=1125 | | ax^2-30x+c=0 | | 100x-1x= |

Equations solver categories